2014
DOI: 10.1007/s11356-014-3632-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of sulfonamides, tetracyclines, quinolones, macrolides, and nitrofurans in livestock manure and amended soils of Northern China

Abstract: A feasible and rapid analysis for the simultaneous determination of sulfonamides (SAs), tetracyclines (TCs), fluoroquinolones (FQs), macrolides (MACs) and nitrofurans (NFs) in livestock manure and soils was established by solid-phase extraction (SPE)-ultra-performance liquid chromatography (UPLC)-tandem mass spectrometry (MS/MS). A total of 32 manure and 17 amended soil samples from the Liaoning and Tianjin areas in Northern China were collected for analysis. The largest detected frequencies and concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(101 citation statements)
references
References 31 publications
8
84
7
2
Order By: Relevance
“…In addition to their application in human medicine, antibiotics are broadly dispensed for therapeutic, prophylactic, and growth promotion purposes in the livestock and poultry industries. Up to 90 % is excreted without being metabolized [4,6], and recent studies have identified as many as 20 different antibiotic compounds in feces samples from swine, poultry, and livestock production facilities [26][27][28][29]. Hospital effluent and wastewater samples are also consistently found to contain a broad range of antibiotic compounds at low concentrations [30,31].…”
Section: Occurrence Of Antibiotics In Soil and Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their application in human medicine, antibiotics are broadly dispensed for therapeutic, prophylactic, and growth promotion purposes in the livestock and poultry industries. Up to 90 % is excreted without being metabolized [4,6], and recent studies have identified as many as 20 different antibiotic compounds in feces samples from swine, poultry, and livestock production facilities [26][27][28][29]. Hospital effluent and wastewater samples are also consistently found to contain a broad range of antibiotic compounds at low concentrations [30,31].…”
Section: Occurrence Of Antibiotics In Soil and Sedimentmentioning
confidence: 99%
“…NH 4 + accumulates in soil as a result of mineralization, N fixation (legumes), direct deposition from the atmosphere, or by application of inorganic fertilizers containing NH 4 + salts, e.g., (NH 4 ) 2 SO 4 . NH 4 + strongly sorbs to the negatively charged surfaces of soil minerals and Ch (1) MM ( [41] Ch (3) SM ( 75.5 [27,28,36,37,41,43,[45][46][47][48][49] soil organic matter (SOM) and is therefore resistant to leaching, but it may be lost by surface runoff, plant uptake, biological nitrification, or annomox reactions. NO 3 − that is produced via nitrification or directly added to soils via inorganic fertilizers, e.g., KNO 3 , is susceptible to a number of losses.…”
mentioning
confidence: 99%
“…This observation is similar to the results of Li et al (2011) who found that most FQs had a detectable ratio of 100% and TC had a detectable ratio of 97%. The investigation of Hou et al (2015) on soils amended with livestock manure also indicated a high detectable ratio of 100% for TCs. Although the SAs have a lower detectable ratio compared with other three types of antibiotics in general, SCZ, SCX and SDM are the three SAs that had a relatively higher detectable ratio.…”
Section: Antibiotics Concentration In the Soils Of Protected Vegetablmentioning
confidence: 96%
“…The veterinary antibiotics may enter soils through landapplication of manures in the farmland and further release into water by runoff or leaching. The veterinary antibiotics contamination in farmland soil has been concerned of worldwide (Kumar et al, 2005;Hu et al, 2010;Li et al, 2011;Hou et al, 2015;Wei et al, 2016). However, the fate of antibiotics in soil varied with compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation